The role of third parties in shaping transboundary cooperation of the Sixaola river basin (Costa Rica and Panama): an analysis through States’ involvement, technocratic turn, and reterritorialization - Bréthaut, Christian; Rodriguez Echavarria, Tania (Frontiers in Water, 2024)
Transboundary water management in the Sixaola basin, shared by Costa Rica and Panama, has historically involved significant contributions from third parties. This study investigates their evolving roles and the implications for governance in this context. We conducted a comprehensive analysis of non-State actors interventions over time, focusing on changes in strategies, priorities, and their impact on transboundary basin governance. Our findings indicate that while non-state actor initiatives have attracted attention and financial resources, they have also introduced significant governance challenges, leading to inconsistencies in basin development. The analysis reveals that limited governmental involvement and the technocratic turn in development strategies have raised questions about basin development and its tangible impacts. Additionally, reterritorialization efforts highlight a local tendency to better align existing functional spaces with local concerns. This study contributes to the literature on transboundary basin management by providing insights into the multifaceted role of non-state actors in the Sixaola basin. It explores a case where governments remain distant in defining governance systems, highlighting the added value of focusing on non-state actors to grasp the complexity of hydropolitics and discussing the politics of river basin development.